A High‐Performance Hierarchical Snapshot Scheme for Hybrid Storage Systems. Issue 1 (1st January 2018) - Yu, Xiao; Tan, Yu'an; Zhang, Changyou; Liang, Chen; Khaled, Aourra; Zheng, Jun; Zhang, Quanxin
Abstract : With the increased snapshot operations (creation or deletion), the performance of storage system will degrade severely whether in Copy on write (COW) or Redirect on write (ROW). This paper presents a novel snapshot scheme which could use of storage resources effectively and keep the historical data accurately for SSDHDD‐hybrid storage system. SSD (source volume) stores all the active data and executes read/write operations without responding to snapshot operations. In contrast, HDDs (snapshot volume) store the writing data sequentially in the form of logs and are responsible for backup and snapshot operations. In this way, the hybrid storage system can get the high throughput power via SSD even the snapshot functions are active and HDDs can keep pace with the high Input/Output operations per second (IOPS) capability of the SSD. Logs are combined and kept in a separate image volume by the controller. So, fine‐grained Recovery point objective (RPO) and good Recovery time objective (RTO) can be achieved. Experiment results show that the prototype can achieve excellent I/O performance while snapshot operations are active and consume a few extra storage space.